Correction: Tanguturi et al. Discovery of Novel Delta Opioid Receptor (DOR) Inverse Agonist and Irreversible (Non-Competitive) Antagonists. Molecules 2021, 26, 6693 - Parthasaradhireddy Tanguturi; Vibha Pathak; Sixue Zhang; Omar Moukha-Chafiq; Corinne E. Augelli-Szafran; John M. Streicher (Molecules, 2022)
There was an error in the original publication [...]